2009
DOI: 10.1093/treephys/tpp063
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine profiles and biosynthesis in somatic embryo development and comparison of germinating somatic and zygotic embryos of Norway spruce

Abstract: The polyamine (PA) contents and activities of PA biosynthetic enzymes in Norway spruce somatic embryos [Picea abies L. (Karst.), genotype AFO 541] were studied in relation to anatomical changes during their development, from proliferation to germination, and changes in these variables associated with the germination of mature somatic and zygotic embryos were compared. Activities of PA biosynthetic enzymes steadily increased during the development of somatic embryos, from embryogenic suspensor mass until early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
2
27
0
3
Order By: Relevance
“…Generally, the development of embryos and their conversion into plantlets is closely associated with changes in endogenous phytohormone levels, including polyamines. Positive correlation between embryogenic capacity and total content of free PAs confirmed to a crucial role of PAs (with Spd predominating, Figs 1, 2, 3) during somatic embryo development in Picea as previously described (Gemperlová et al, 2009; S.C. Minocha & Long, 2004). On transfer from proliferation to maturation medium the levels of Put and Spd in the culture of highly responsible cell line AFO 541 were almost equal while in less responsible cultures of Hurst ecotype significantly higher levels of Put than Spd were determined as is apparent from the Put/Spd ratios in the embryogenic suspensor masses (ESM) of six cell lines of Norway spruce (AFO 541 and five of Hurst ecotype) grown on solid proliferation medium (Figs 1, 2).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Generally, the development of embryos and their conversion into plantlets is closely associated with changes in endogenous phytohormone levels, including polyamines. Positive correlation between embryogenic capacity and total content of free PAs confirmed to a crucial role of PAs (with Spd predominating, Figs 1, 2, 3) during somatic embryo development in Picea as previously described (Gemperlová et al, 2009; S.C. Minocha & Long, 2004). On transfer from proliferation to maturation medium the levels of Put and Spd in the culture of highly responsible cell line AFO 541 were almost equal while in less responsible cultures of Hurst ecotype significantly higher levels of Put than Spd were determined as is apparent from the Put/Spd ratios in the embryogenic suspensor masses (ESM) of six cell lines of Norway spruce (AFO 541 and five of Hurst ecotype) grown on solid proliferation medium (Figs 1, 2).…”
Section: Resultssupporting
confidence: 83%
“…PAs changes were studied in embryogenic cultures of Picea abies (R. Minocha et al, 1993;Serapiglia et al, 2008;Vondráková et al, 2010), Picea rubens (R. Minocha et al, 1993), Pinus taeda (Silveira et al, 2004), and P. radiata (R. Minocha et al, 1999). Polyamine profiles in germinating somatic embryos derived from long term cultivated embryogenic mass and germinating zygotic embryos of Norway spruce were studied by Gemperlová et al (2009). There are also several reports indicating the participation of PAs in somatic embryo development of some coniferous species (R. Minocha et al, 1999;Santanen & Simola, 1992;Silveira et al, 2004) but the mechanism of how polyamines regulate cell differentiation processes is not fully elucidated up to the present.…”
Section: Introductionmentioning
confidence: 99%
“…(Karst.) (Gemperlová et al 2009). Somatic embryos displayed more total free PAs than zygotic embryos which indicated that PA metabolism is quite different in these two tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of total lipids exhibited marked variation during maturation of Picea abies somatic embryos, indicating the importance of lipid reserves during embryo development (Svobodová et al 1999, Grigová et al 2007). The accumulation of high levels of polyamines in Picea abies somatic embryos may be causally linked to their lower germinability than in zygotic embryos (Gemperlová et al 2009). Endogenous levels of IAA decreased in the period of embryo development and increased again in the late maturation stage.…”
Section: Biochemistry Of Zygotic and Somatic Embryosmentioning
confidence: 99%